Analisis Perilaku Mahasiswa dalam Menemukan Literatur Rujukan Materi Diskusi Tutorial Online - Hascaryo Pramudibyanto (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2024)
This research analyzes students' behavior in searching for reference literature in online tutorial discussions, highlighting various approaches used in deepening understanding of learning materials. The results indicate that students actively utilize online tutorials as their primary source to enhance understanding and skills related to the courses they are taking, as well as actively participate in online discussions. However, some students exhibit less active participation, indicating variations in student engagement in online learning. Some factors influencing low participation include differences in learning preferences and time constraints. Therefore, it is recommended to develop clear participation guidelines, provide incentives to active students, and develop more interactive learning methods in online tutorials. Additionally, educational institutions should provide strong technical support to students to ensure active participation. These efforts are expected to enhance the quality of learning and interaction among members of the academic community in online learning.